Managing economic and Islamic research in big data environment: from computer science perspective / Nordin Abu Bakar - Abu Bakar, Nordin (Faculty of Business and Management, Universiti Teknologi MARA, Selangor, 2018)
Research in economic and Islamic fields are facing a major challenge in the surge of big data. The landscape and the environment produce problems of massive magnitude and demand robust solutions. The traditional method might not be able to cater for this huge challenge; so, researchers must embark on the mission to seek new and versatile methods to solve the complex problem. If not, the research output would end up with sub-optimal results. In computer science, there are machine learning algorithms that have been used to solve problems in a such complex environment. This article explains the current demanding situation facing many researchers and how those algorithms have successfully solved some of the problems. The potential applications of the methods should be learned and utilised to improve the outcome of the research in these fields